Caregiving for Intellectual Disability: A Burden Analysis of the Primary Family Caregivers (Journal of Psychiatrists' Association of Nepal, 2025)
Background: Caregiving for individuals with intellectual disability (ID) often places a significant burden on primary family caregivers, as it requires lifelong care and support. This demanding role can lead to physical, emotional, and financial strains, collectively referred to as "caregiver burden."Objectives: This study was conducted to identify who serves as a primary caregiver in the family, the caregiver burden experienced by caregivers of intellectually disabled people, and other associated factors.Methods & Materials: A cross-sectional quantitative study was conducted, using purposive sampling. A sample of 50 primary caregivers was included in this study. The data collection tools used were the Burden Scale for Family Caregivers (BSFC-s) and the Vineland Social Maturity Scale (VSMS). The translated Nepali version of the BSFC-s was used after the validation process. The Vineland Social Maturity Scale was used in its original form, as it is typically administered by clinicians through interviews with informants.Results: The data indicate that 92% of primary caregivers are mothers, with 60% having no formal education bearing the majority of caregiving responsibilities. The majority (74%) experienced severe to very severe burden, while 24% reported moderate burden. Only 2% experienced mild to no burden. The analysis revealed a significant positive correlation between caregiver burden and patient IQ (r = 0.419, p = 0.002). Caregivers with secondary support report significantly lower burden levels compared to those without support (M = 2.58-3.00, p = .003).Conclusion: In the Nepalese population studied, primary caregivers, mostly mothers, faced severe burden, which was significantly linked to patient IQ and eased by secondary support. The study highlights the urgent need for support systems in Nepal to reduce caregiver burden among those caring for individuals with intellectual disabilities, informing by forming policies and healthcare interventions.